Komunikasi Interpersonal dalam Mencegah Konflik Antar Suku - Usman, Yogi Birmana; Ningsih, Astuti Patmi (Ath Thariq Jurnal Dakwah dan Komunikasi, 2023)
Indonesia is a country with a multi-ethnic population; diverse ethnicities, religions and races. Diversity is an interesting thing to maintain while maintaining mutual respect and respect for each other. The diversity that exists if there is no mutual respect and respect will cause conflicts that can divide the unity of the nation itself. Research that discusses conflict has been done before, but related to conflicts in Kedaton Induk Village has not been carried out, so it is interesting to do. This study aims to determine how important interpersonal communication is in preventing conflicts between indigenous tribes, Lampung communities and transmigrant communities in Kedaton Induk Village, Batanghari Nuban District, East Lampung. This field research uses a qualitative approach, explaining the phenomena that occur in the field by collecting data obtained from resource persons in the Kedaton Induk village community, collecting research data using observation, interviews and documentation. The results of this study show that interpersonal communication in Kedaton Induk Village is applied by village officials, both village heads, bambimkamtibmas, community leaders to all residents in Kedaton Induk Village in order to prevent inter-tribal conflicts that have occurred before. Intense interpersonal communication is carried out both directly and indirectly (using media) with the aim of avoiding misunderstandings. The local government provides a policy so that villagers use Indonesian as the national language and can be understood by all residents in Kedaton Induk Village. Communication is carried out through young face-to-face with the community or using media that are already known to residents such as telephone, SMS or WhatsApp to convey information so that misunderstandings do not occur which can lead to conflicts again. In addition, holding activities with all residents when celebrating the seventeenth of August Independence Day, and other activities.